Association Between Inflammatory Bowel Disease and Psychiatric Morbidity and Suicide: A Swedish Nationwide Population-Based Cohort Study With Sibling Comparisons. (27th February 2021) - Ludvigsson, Jonas F; Olén, Ola; Larsson, Henrik; Halfvarson, Jonas; Almqvist, Catarina; Lichtenstein, Paul; Butwicka, Agnieszka
Abstract: Background and Aims: Inflammatory bowel disease [IBD] is linked to psychiatric morbidity, but few studies have assessed general population comparators. We aimed to investigate the risk of psychiatric morbidity and suicide in adult-onset IBD patients. Methods: We used a nationwide population-based cohort study in Sweden [1973–2013]. We studied the risk of psychiatric disorders and suicide in 69, 865 adult-onset IBD patients [ulcerative colitis, UC: n  = 43, 557; Crohn's disease, CD: n  = 21, 245; and IBD-unclassified: n  = 5063] compared to 3, 472, 913 general population references and 66 292 siblings. Results: During a median follow-up of 11 years, we found 7465 [10.7%] first psychiatric disorders in IBD [incidence rate, IR/1000 person-years 8.4] and 306 911 [9.9%] in the general population [IR 6.6], resulting in 1.8 extra psychiatric morbidity per 100 patients followed-up for 10 years and a hazard ratio [HR] of 1.3 [95% confidence interval, 95%CI = 1.2–1.3]. The highest risk of overall psychiatric morbidity was seen in the first year after IBD diagnosis [HR = 1.4, 95%CI = 1.2–1.6] and in patients with extraintestinal manifestations [HR = 1.6, 95%CI = 1.5–1.7]. Psychiatric morbidity was more common in all IBD subtypes [HR 1.3–1.5]. An increased risk of suicide attempts was observed among all IBD types [HR = 1.2–1.4], whereas completed suicide was explicitly associated with CD [HR = 1.5] and elderly-onset [diagnosed at the age of > 60 years] IBD [HR = 1.7]. Conclusion: Adult-onset IBD was associated with an increased risk of psychiatric disorders and suicide attempts. Psychological follow-up should be provided to patients with IBD, especially those with extraintestinal manifestations and elderly-onset IBD. This follow-up should be within the first year after IBD diagnosis.